Training afrodescendant women teachers. Condition and teaching profession in the inconfidentes region - Lima Jardilino, Jose Rubens; Diniz, Margareth (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article presents reflections on the trajectories of Afrodescendant women teachers in the “Inconfidentes” region in the state of Minas Gerais in southeastern Brazil. The research was conducted by means of narratives and life histories of rural teachers through the research method: conversation analysis. Categories of gender and race were used and as a frame of reference we had into account the construction of the various identities that help teachers to develop their careers. The results have shown that research subjects, women teachers of basic education in the region, have some difficulty in integrating the identities of race and gender into their educational and social practices.